Estimation of the prevalence of the main reproductive pathologies that affected dairy farming in Colombia reported between 2019 and 2022 through a meta–analysis - Laura Marcela Moreno–Andrade; Nelitza Linárez–Álvarez; Adriana María Pedraza–Toscano; Orlando Alfredo Torres–García; Francisco Javier Vargas–Ortiz; Ignacio de Blas–Giral (Revista Científica)
Reproductive pathologies in dairy cattle significantly impact animal welfare, profitability, and productivity. The objective of this study was to estimate the prevalence of the main reproductive pathologies that have affected livestock farming in Colombia during the period between 2019 and 2022 through a systematic review and meta–analysis. A meta–analysis was carried out where the prevalence of diseases was identified, where initially a systematic review was accomplish with the PRISMA methodology, using the databases PubMed, Science Direct, Dialnet, Google Scholar. Inclusion and exclusion criteria were defined, the quality of the studies was evaluated and data was extracted from the selected articles to analyze the information using the OpenMeta [Analyst]® software, in order to standardize the findings obtained. From an initial 3,883 bibliographic references, 28 studies met the inclusion criteria. Infectious Bovine Rhinotracheitis (IBR) exhibited the highest prevalence, ranging from 0.00% to 77.30%, followed by Bovine Neosporosis (17.55% – 61.34%) and Bovine Viral Diarrhea (BVD) (16.14% – 44.13%). Brucellosis (0.01% – 1.65%) and Leptospirosis (1.48% – 24.33%) displayed the lowest overall prevalence. Data for other reproductive diseases was either absent or excluded based on the defined criteria. The identified prevalence of reproductive diseases in Colombian dairy cattle highlights the need for improved farm health protocols and management practices. Furthermore, a scarcity of studies across different regions suggests a gap in knowledge regarding the true national prevalence of these diseases. This knowledge is crucial for establishing effective health and animal welfare plans.